Professional Clinical Bioethics: The Next Generation - Potter, Jordan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This commentary details the shortcomings of the traditional healthcare ethics committee model in modern healthcare and argues for the necessity of professional clinical bioethicists to better meet modern healthcare’s ethics needs.